Causes of losses and the economic loss estimates at post-harvest handling points along the beef value chain in Uganda - Kyayesimira, Juliet; Rapheal, Wangalwa; Rugunda, Kagoro Grace; Bunny, Lejju Julius; Matofari, Joseph W; Andama, Morgan (Journal of Agricultural Extension and Rural Development, 2019)
Uganda’s beef industry has been growing slowly and requires sustained monitoring of actors at post harvest handling points in order to decrease public health risks and losses. This study documented causes of losses and estimated economic values at post-harvest handling points along the beef value chain. It was carried out at slaughter houses, transporters and butcher shops in the districts of Western, Central and Eastern Uganda. A cross sectional study was conducted among meat handlers who were interviewed to find out the losses incurred in the value chain. Microbial load from carcass swabs were collected and evaluated using standard microbiological methods to determine microbial contamination of beef. The causes of losses varied at different handling points. The actors at slaughter houses indicated the major losses were due to low beef demand (15.3%), insecurity (13.4%) and poor weight estimation methods (11.03%). Losses at the butchery included, beef waste (22.4%), drip loss (19.7%) and beef spoilage (18.4%). Microbial analysis showed the highest microbial prevalence at the butchery (70-100%) followed by slaughter (50-80%) and lastly transport (30-50%). Microbial contamination on carcass leads to spoilage and hence market loss because exportation does not admit contaminated foods. Actors reported beef waste and drip loss as the major causes of losses at the butchery. To reduce losses, public health care education for meat handlers and adherence to strict standard operating procedures (SOPs) are a key
Keywords: Losses; post-harvest; beef value chain; handling points; Uganda